The Effectiveness of Using Online Module Based on E-Learning on Elementary School Teacher Study Program at Faculty of Teacher Training and Education, Universitas Syiah Kuala - Mislinawati Mislinawati; Intan Safiah; Nurmasyitah Nurmasyitah (Proceedings of AICS - Social Sciences, 2021)
Many obstacles have been discovered since the implementation of online lectures, particularly in the provision of teaching materials in the form of modules, which is still very limited, even though all lecturers are required to input material in the form of modules into eLearning.unsyiah.ac.id. The availability of online-based modules is one of the significant components of online learning. The goal of this study was to see if the implemenation of online modules for PGSD students was effective. The research applieds a quantitative approach, employing a survey method with the sample of 40 students from the PGSD FKIP USK study program of FKIP USK. According to the findings, 60% of the students improved their understanding of the information offered in the module,; 55% were more disciplined in submitting assignments,; and 72% indicated that lectures were helpful and motivating using e-learning-based modules. In conclusion, the use of online modules based on e-learning for PGSD FKIP USK students was considered effective.Keywords: Effectiveness, e-learning, and online module.